Comparison of dopamine versus norepinephrine in circulatory shock after cardiac surgery: A randomized controlled trial. Issue 10 (26th July 2021) - Lim, Ju Yong; Park, Sung Jun; Kim, Ho Jin; Kim, Hee Jung; Choo, Suk Jung; Chung, Cheol Hyun; Lee, Jae Won; Park, Duk‐Woo; Kim, Joon Bum
Abstract: Background and Aim of the Study: Although dopamine and norepinephrine are recommended as first‐line agents in the treatment of shock, it is unclear which is the optimal vasoactive inotropic agent (VIA) to manage postcardiotomy circulatory shock. This single‐center, randomized clinical trial aimed to investigate the efficacy and safety of dopamine versus norepinephrine in postcardiotomy circulatory shock. Methods: We randomly assigned the patients with postcardiotomy circulatory shock to receive either dopamine or norepinephrine. When shock persisted despite the dose of 20 μg/kg/min of dopamine or the dose of 0.2 μg/kg/min of norepinephrine, epinephrine or vasopressin could be added. The primary endpoint was new‐onset tachyarrhythmic event during drug infusion. Secondary endpoints included requirement of additional VIAs, postoperative complications, and all‐cause mortality within 30 days of drug initiation. Results: At the planned interim analysis of 100 patients, the boundary for the benefit of norepinephrine has been crossed, and the study was stopped early. Excluding two patients withdrawing a consent, 48 patients were assigned to dopamine and 50 patients to norepinephrine. New‐onset tachyarrhythmic event occurred in 12 (25%) patients in the dopamine and one (2%) patient in the norepinephrine group ( p  = .009). The requirement for additional VIAs was more common in the dopamine group ( p  < .001). Other secondary endpoints were similar between groups. Conclusions: Despite the limited study subjects with early determination, in patients with postcardiotomy circulatory shock, dopamine as a first‐line vasopressor was associated with higher tachyarrhythmic events and greater need for additional VIAs compared with norepinephrine.